Two Modes Bifurcation Solutions of Elastic Beams Equation with Nonlinear Approximation - Hussain, Mudhir A. Abdul (Communications in Mathematics and Applications, 2010)
In this paper we studied two modes bifurcation solutions of elastic beams equation by using Lyapunov-Schmidt method. The bifurcation equation corresponding to the elastic beams equation has been found. Also, we studied two modes of nonlinear approximation of bifurcation solutions of a specified equation and we found the Key function corresponding to the functional related to this equation.